Haddul Kifayah: Its comprehensiveness, sufficiency and currency in meeting the needs of the asnaf faqr and asnaf miskin - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Ahmad Sarkawi, Azila (2015)
Haddul kifayah refers to the income of an individual or household, used by zakat authorities, in determining whether an individual or household are eligible to be categorized as asnaf faqr or asnaf miskin. Consequently, if they fit into any one of the said asnaf, they would be eligible to be given financial assistance via the zakat fund. This paper reports a desk study and interviews with representatives of the relevant zakat authorities in examining the haddul kifayah in terms of its legitimacy in accordance to the shari’ah, the method used in determining the level of income, factors and components included therein and the currency of the resulting amount. In addition, by contrasting the haddul kifayah with the official Poverty Line Income (Pendapatan Garis kemiskinan) and its factors and components thereto the study attempts to establish whether the approach adopted in determining the haddul kifayah is considered appropriate, comprehensive and sufficient vis-à-vis the current cost of living. In the course of the study, key issues related to the haddul kifayah were identified and highlighted in this paper. The paper concludes with recommendation on how the approach in determining the haddul kifayah could be further improved especially in the lights of newer and future challenges facing the Muslim ummah.